The relationship between job characteristics and work family enrichment - Le Shauls, Bridgette (School of Management Studies, 2024)
This study examined job characteristics as antecedents of work-family enrichment amongst full time employees in an investment company in South Africa (N = 129). Contrary to expectations of work family enrichment having three underlying dimensions, an exploratory factor analysis revealed a unidimensional construct. Multiple regression analysis evidenced that a higher level of work-family enrichment was reported by respondents in jobs where feedback and friendship were experienced. There was no support for the hypotheses that employees in jobs with more autonomy, task identity and/or dealing with others, would experience greater work-family enrichment. Management implications of these results and future directions for research are discussed.